On the use of residual dipolar couplings in multi-state structure calculation of two-domain proteins - Born, Alexandra; Henen, Morkos A.; Nichols, Parker J.; Vögeli, Beat (Magnetic resonance letters, 2022)
Residual dipolar couplings (RDCs) are powerful nuclear magnetic resonance (NMR) probes for the structure calculation of biomacromolecules. Typically, an alignment tensor that defines the orientation of the entire molecule relative to the magnetic field is determined either before refinement of individual bond vectors or simultaneously with this refinement. For single-domain proteins this approach works well since all bond vectors can be described within the same coordinate frame, which is given by the alignment tensor. However, novel approaches are sought after for systems where no universal alignment tensor can be used. Here, we present an approach that can be applied to two-domain proteins that enables the calculation of multiple states within each domain as well as with respect to the relative positions of the two domains. The use of residual dipolar couplings in multi-state structure calculation with two-domain proteins is challenge. Here we present a protocol that relies on a two-step calculation using alignment tensors of both domains. [Display omitted]